Narrowband-to-Narrowband Frequency Reconfiguration with Harmonic Suppression Using Fractal Dipole Antenna - S. A. Hamzah; M. Esa; N. N. N. A. Malik; M. K. H. Ismail (International Journal of Antennas and Propagation)
Harmonic suppressed fractal antenna with switches named TMFDB25 is developed to select desired frequency band from 400 MHz to 3.5 GHz. The radiating element length is changed to tune the operating frequency while the stub is used to eliminate the undesired harmonic frequency. The balun circuit is reduced by 75% from the original size. The antenna is built on a low loss material. It has the ability to select a single frequency out of fifteen different bands and maintain the omnidirectional radiation pattern properties. Furthermore, the antenna is designed, built, and tested. Simulation and measurement results show that the antenna operates well at the specific frequency range. Therefore, the antenna is suitable to be used for switching frequencies in the band of TV, GSM900/1800, 3G, ISM 2.4 GHz, and above.